Exergames as a Tool for Improving Muscular Fitness, Cardiorespiratory Fitness, and Body Composition in Children and Adolescents: A Systematic Review; [Exergames Para Mejorar la Condición Física y la Composición Corporal en la Niñez y Adolescencia: Una Revisión Sistemática] - Poblete-Aro, C (Federacion Espanola de Docentes de Educacion Fisica, 2025)
Introduction: over 80% of children and adolescents fail to meet physical activity recommendations, leading to declines in muscular and cardiorespiratory fitness and rising obesity rates. Exergames—digital games requiring physical movement—are a promising tool to promote activity in youth. Objective: to determine the effects of exergames on muscular fitness, cardiorespiratory fitness, and body composition in children and adolescents. Methodology: a search was conducted in Web of Science, Scopus, CINAHL, and PubMed databases, including randomized controlled trials published in the last 10 years. Studies were excluded if they involved participants with disabilities or used exergames for rehabilitation or hospital-based interventions. Results: a total of ten studies were included: three out of five studies reported improvements in muscular fitness, seven out of nine in cardiorespiratory fitness, and five out of nine in body composition. The most effective interventions occurred 2–3 times per week, for 40–60 minutes per session, over at least 12 weeks. Discussion: while outcomes are promising, differences in study design, duration, and assessment tools may have affected consistency across results. Conclusion: exergames appear effective for improving health-related fitness in children and adolescents, providing a fun and accessible way to increase physical activity through technology. © 2025 Federacion Espanola de Docentes de Educacion Fisica. All rights reserved.